Not just for show - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Ornamental plant propagation in the tropics FAO, 2000. 84 pp. ISBN 9251044600 US$ 14 Euro 14.95